PENINGKATAN KETERAMPILAN MERANGKAI BUNGA PAPAN MELALUI MEDIA PEMBELAJARAN VIDEO TUTORIAL PADA SISWA DISABILITAS INTELEKTUAL RINGAN - Gusrita, Mei; Damri, Damri; Rahmahtrisilvia , Rahmahtrisilvia; Yuliana, Syari (STKIP Pesisir Selatan, 2025)
The study was motivated by low learning interest and limited independence achievement among students due to instructional practices that were predominantly based on verbal explanations and direct demonstrations without the support of varied learning media. This research employed a Classroom Action Research (CAR) design using both qualitative and quantitative approaches and was conducted at SLB Aslam Kids Padang. The research subjects were Grade X students with mild intellectual disabilities. The study was implemented in two cycles, each consisting of four meetings and following the stages of planning, action implementation, observation, and reflection. Data were collected through structured observations of students’ learning activities and assessments of flower board arrangement skills, while data analysis was conducted using percentage techniques. The results indicated that the use of video tutorial media significantly improved students’ learning activities and skill performance. The average percentage of students’ activity and skill achievement increased from 68.7% in Cycle I to 93% in Cycle II. The novelty of this study lies in the use of video tutorial media as a vocational learning intervention that is visually structured, step-by-step, and repeatable according to students’ needs, effectively supporting the learning characteristics of students with mild intellectual disabilities in achieving greater learning independence.